The Implementation of Care Coordination Model Toward Delivery of Quality Care in Private Hospital Outpatient Setting - Ricca, Rica; Antonio, Ferdi (Universitas Pelita Harapan, 2021)
Health care services in the private hospitals are required to deliver quality care to stay competitive in the business. In line with the advancement of hospital facilities and the raise of patient needs for complex care, the care coordination is inevitable to ensure the delivery quality of care. The purpose of this study is to test and analyze the care coordination model toward delivery of quality care in the private hospital outpatient setting. This research model was empirically tested on outpatient clinic at one of the leading hospitals in Indonesia. The data was analyzed by PLS-SEM method, whereas respondent obtained by purposive sampling technique. The result of structural model, shown moderate to strong prediction accuracy with large predictive relevance indicate and acceptable model. The result demonstrated that all of care coordination paths lead to the delivery of quality care has significant positive effect, except for facilitate transitions and accountability to communication and information transfer. However, facilitate transitions and accountability has significant positive effect through IT-enabled care coordination and through interprofessional teamwork and consistency. Therefore, it could be concluded that all variables have contribution to the care coordination in the outpatient, respectively. The strongest direct effect to care quality perception is found from communication and information transfer, while the strongest indirect effect is from physical infrastructure and facilities which mediating by IT-enabled care coordination and further communication and information transfer. There are managerial implications that could give suggestions for hospital managers to improve care coordination process in hospital outpatient services.